2019
DOI: 10.22219/jaa.v2i2.8976
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Employee Stock Option Plan on Market Performance With Firm Performance as Intervening Variable

Abstract: ABSTRAKEmployee Stock Option Plan (ESOP) merupakan surat kontrak dimana perusahaan akan memberikan hak kepada karyawannya untuk dapat membeli saham perusahaan dengan harga dan waktu tertentu. Program ini merupakan bentuk kompensasi yang dapat memotivasi serta menyelaraskan tujuan yang dinginkan oleh pihak prinsipal dan agen. Adanya kesamaan tujuan utama yang ingin dicapai akan memudahkan perusahaan dalam upaya peningkatan kinerja pasar perusahaan. Hubungan pengaruh antara ESOP dan kinerja pasar dapat dimediasi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0
1

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 2 publications
0
3
0
1
Order By: Relevance
“…Regarding the compensation program as a form of company reward to management, this study proved that this program co u l d increase employees' teamwork in the organizational structure to improve company performance (Laudya & Handoko, 2019).…”
Section: Impact Of Stock-based Compensation On the Effect Of Capital ...mentioning
confidence: 74%
See 2 more Smart Citations
“…Regarding the compensation program as a form of company reward to management, this study proved that this program co u l d increase employees' teamwork in the organizational structure to improve company performance (Laudya & Handoko, 2019).…”
Section: Impact Of Stock-based Compensation On the Effect Of Capital ...mentioning
confidence: 74%
“…Ramchandani & Pandya (2019) shows that the success of ESOP companies in countries such as the United States, Japan and the UK supports improving company performance and employee productivity. However, research conducted by Laudya & Handoko (2019) showed contradictory results because the ESOP program did not support the company's financial performance. The novelty of this research is based on the main challenge of this research, namely developing more comprehensive, objective, and reliable research by considering the moderating variable is the implementation of long-term stock-based compensation especially employee stock options which will be able to support the influence of intellectual capital on company performance.…”
Section: 2mentioning
confidence: 99%
See 1 more Smart Citation
“…Sesuai dengan fenomena yang terjadi, dilansir dari liputan6.com bahwa karyawan bank BCA menuntut adanya kenaikan gaji (Praditya, 2014). Salah satu solusi untuk meningkatkan kinerja karyawan dalam mencapai tujuan perusahaan dengan memberikan reward (Laudya & Handoko, 2019). Reward berupa pemberian saham melalui employee stock ownership program diyakini mampu meningkatkan loyalitas karyawan, karena seolah karyawan mendapatkan bagian tersendiri dalam kepemilikan saham (Sukmawijaya, 2018).…”
unclassified